PERENCANAAN STRATEGIS SISTEM INFORMASI PERGURUAN TINGGI - Henderi, Henderi (Bina Nusantara University, 2009)
Strategic planning of information systems is to establish policy and planning implementation of information technology as a supporter of bussiness process and solution of the problem with high accuracy and know the possibilities of the system is less precise procedure. To achieve this, an information systems strategy planning organizations (including universities therein) should be done through the stages: an analysis of objectives and issues / information needs (goals and poblem), critical success factor (CSFs), SWOT analysis, impact analysis information technology (technology impact analysis) and analysis of the vision or strategic view of the system (strategy vision system) and a review model of business functions (business proccess) organization. In STMIK Raharja, strategic planning and information system model was developed based on through these stages and includes information services to be provided by STMIK Prog as a university. Determination of information system strategic planning and selection of models developed subsequently determined by the specific needs and determinants with attention to rules and procedures. This paper presented a discussion about the foundation and information systems strategic planning phases of Higher Education as an organization by taking a model of information services at Raharja STMIK Tangerang, with academic information subsystem as an example the case of the implementation of the development. To clarify the discussion, at this writing are also discussed briefly about the strategy on information systems implementation STMIK Prog as a university organization.Keywords: critical success factor, model, business process, strategy system vision